The Usefulness of Demand Forecasts for Team Resource Allocation in a Dynamic Environment - Groves, Theodore (Review of Economic Studies, 1983)
The efficiency of market information for planning resource allocation in "real time" is explored. In each period resources are allocated as planning for the next period proceeds. Full optimality is not possible, even when maximum information is exchanged between firms and resource allocators, as the technologies of the firms are changing. The major result shows that market-type information such as demands and especially demand forecasts is as good as full technological information to exchange.